Patients with a History of Treated Septic Arthritis are at High Risk of Periprosthetic Joint Infection after Total Joint Arthroplasty. Issue 7 (July 2019) - Sultan, Assem A.; Mahmood, Bilal; Samuel, Linsen T.; George, Jaiben; Faour, Mhamad; Pelt, Christopher E.; Anderson, Mike B.; Klika, Alison K.; Higuera, Carlos A.
Abstract: Background: In patients undergoing total joint arthroplasty (TJA), increasing attention has been directed recently toward identifying specific patient-related risk factors that may predispose patients to periprosthetic joint infection (PJI). Currently, it is unclear whether having a history of a treated native septic arthritis is a risk factor for PJI after TJA in the same joint. Previous studies have reported contradictory evidence and results varied between a substantially higher rates of PJIs to very low or no reported PJIs. Questions/purposes: (1) What is the risk of PJI in patients who received TJA and had a history of treated same-joint native joint septic arthritis and (2) What are the associated risk factors for these patients developing PJI? Methods: This was a multicenter retrospective analysis of patients who received primary THA or TKA between January 2000 and December 2016 and who had a history of treated native joint septic arthritis in the same joint. Patients were included in the study only if they were considered to have resolved their joint infection based on a preoperative evaluation that included: (1) the absence of clinical symptoms and signs of active infection or local joint inflammation, (2) recent plain radiographs showing only advanced degenerative changes without evidence of active osteolysis or bone infection, (3) preoperative laboratory investigations for infection, including erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and total leukocyte counts within normal ranges. Patients were reviewed for the occurrence of postoperative PJI. The final cohort included 62 patients who had a mean followup of 4.4 years (range, 3 months–17 years) from the time of TJA. A total of 21 patients (34%) had less than 2 years of followup, including six (10%) mortalities. In total, eight patients (13%) died during the study period, none of which were due to PJI. Patient characteristics, time interval from treatment of septic arthritis to TJA, and Charlson comorbidity index adjusted for age were collected. We used a Kaplan-Meier analysis to estimate the overall survivorship among all TJAs as well as those who underwent THA versus TKA, and we performed a statistical comparison using the Mantel-Cox log-rank test. We performed a Cox regression hazard ratio (HR) survival analysis to identify risk factors for PJI. The PJI odds ratios (OR) for patients who underwent TJA within 2 years of septic arthritis were calculated as an additional temporal analysis. Results: In patients with a history of treated same-joint native septic arthritis, the proportion of PJI was five of 62 patients (8%). The Kaplan-Meier analysis demonstrated an overall survivorship free from PJI of 92% at 14.5 ± 1.14 years (95% confidence interval [CI] = 12.3–16.8 years). All PJI cases occurred only in patients who underwent TKA, which when analyzed separately, yielded a survivorship of 85% at 10.5 ± 0.9 years (95% CI = 8.7–12.3 years) versus 100% in patients who underwent THA (p = 0.068). Mean time to PJI occurrence was 10 months (range, 2–20 months). After controlling for relevant confounding variables, such as age, sex, affected joint and comorbidities, we found smoking (HR, 8.06; 95% CI, 1.33–48.67; p = 0.023) to be associated with increased risk for PJI development. Conclusion: Patients with history of native joint infections are at higher risk of PJI, especially smokers. Despite our limitations, this study suggests careful assessment of several other factors in these patients, including allowing a minimum interval of 2 years from the time of resolving native joint septic arthritis to TJA. Patients who are undergoing TKA seem to be more prone to the PJI risk and may benefit from more aggressive planning. In addition, medical optimization of comorbidities that may confer additional risk, such as diabetes, become exceptionally important in these patients. Level of Evidence: Level III, therapeutic study.